REVIEW OF THE INTERNATIONAL PRACTICE OF COST-SHARING MECHANISM IN NATIONAL HEALTH CARE SYSTEMS - Natalia Nikolayevna Sisigina; Vitalii Vladimirovich Omel'yanovskii; Nikolay Alexandrovich Avxentyev (Фармакоэкономика)
The article gives a review of international experience of using of cost-sharing mechanism to prevent the risk of patient’s moral hazard. Theoretical background and types of cost-sharing, protection mechanisms for vulnerable social groups, national cost-sharing models are considered.